2016
DOI: 10.29069/forscience.2016v4n1.e182
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre gerenciamento de resultado e governança corporativa: construindo um referencial teórico a partir de uma revisão sistemática da literatura

Abstract: RESUMOEste trabalho teve como objetivo realizar uma revisão sistemática nos estudos que relacionam gerenciamento de resultado e governança corporativa. A pesquisa dos artigos foi efetuada no Portal de Periódicos da Capes e também nas bases Scopus, ScienceDirect, Web of Science e SciELO. A busca identificou um total de 171 artigos, e, depois de uma análise, foram selecionados 41 para este estudo. A revisão sistemática demonstrou que a maioria dos estudos defende que a governança corporativa reduz o gerenciament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
3
0
1
Order By: Relevance
“…Therefore, relying on quantitative techniques, this sort of analysis allows the possibility to unveil significant aspects, such as the citations, co‐citations, authors, co‐authors, periodicals, keywords, among other characteristics, such as the growth and distribution of the bibliographic production (Hsu and Chiang, ; Sanchez‐Riofrio et al. , 2015; Costa and Carvalho, ; Prado et al. , 2016; Costa et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, relying on quantitative techniques, this sort of analysis allows the possibility to unveil significant aspects, such as the citations, co‐citations, authors, co‐authors, periodicals, keywords, among other characteristics, such as the growth and distribution of the bibliographic production (Hsu and Chiang, ; Sanchez‐Riofrio et al. , 2015; Costa and Carvalho, ; Prado et al. , 2016; Costa et al.…”
Section: Methodsmentioning
confidence: 99%
“…The bibliometric analysis should be systematic, in other words, it must be based on primary studies, it must encompass goals and methods that are clearly stated, it also should be conducted using a clear and reproducible methodology (Greenhalgh, 1997). Therefore, relying on quantitative techniques, this sort of analysis allows the possibility to unveil significant aspects, such as the citations, co-citations, authors, co-authors, periodicals, keywords, among other characteristics, such as the growth and distribution of the bibliographic production (Hsu and Chiang, 2015;Sanchez-Riofrio et al, 2015;Costa and Carvalho, 2016;Prado et al, 2016;Costa et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…For Mazzioni, Prigol, Moura & Klann (2016), who examined the influence of corporate governance and capital structure in the earnings management of public companies listed on the BM&FBovesta (2010-2013), the influence of corporate governance to reduce earnings management was observed ASAA only in 2010. Additionally Costa & Carvalho (2016) made a systematic review on the studies related to earnings management and corporate governance showed that most of the studies state that corporate governance reduces the earnings management. In this point of view is possible to affirm that the one of the objectives of corporate governance is to improve the quality of accounting information, which in general occurs, according to papers cited above.…”
Section: Overview Of the Earning Qualitymentioning
confidence: 99%
“…A realização desse tipo de investigação é composta de cinco estágios: (i) definição dos termos e dos métodos de busca; (ii) definição das bases de dados; (iii) seleção dos artigos; (iv) levantamento dos principais pontos de cada artigo; e (v) análise dos resultados (Costa & Carvalho, 2016).…”
Section: Introductionunclassified